Nutritional Composition and Health Benefits of Golden Grain of 21st Century, Quinoa (Chenopodium quinoa willd.): A Review - Arneja, Intelli; Tanwar, Beenu; Chauhan, Ambika (Pakistan Journal of Nutrition, 2015)
Quinoa (Chenopodium quinoa willd.), a pseudo-cereal, has its origin from Andes region of South America. Its exceptional nutritional content, potential health benefits and crop’s tolerance to adverse climatic conditions inspire nutritionists and researchers worldwide to explore more about this "wonder grain". Reviewers till now have focused on composition of this underutilized grain but extensive research work has now proved potential health benefits of quinoa. The present review covers recent research information on quinoa especially its potential health benefits to humans and also its nutritional content. Gluten free grain quinoa has been found to exhibit anti oxidative, anti hypertensive, anti diabetic properties hence can be used as nutraceutical and functional food ingredient.